2017
DOI: 10.1111/ahe.12270
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Neural Differentiation Potential of Canine Adipose Tissue-Derived Mesenchymal Stem Cells

Abstract: Adipose tissue-derived stem cells (ASCs) can be obtained from different adipose tissue sources within the body. It is an abundant cell pool, easily accessible, suitable for cultivation and expansion in vitro and preparation for therapeutic approaches. Amongst these therapeutic approaches are tissue engineering and nervous system disorders such as spinal cord injuries. For such treatment, ASCs have to be reliably differentiated in to the neuronal direction. Therefore, we investigated the neural differentiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 49 publications
5
18
0
Order By: Relevance
“…i.e. 2×10 6 /1 kg of body mass, based on reports published by other authors and our own clinical observations (10,15,20,21,22).…”
Section: Methodsmentioning
confidence: 84%
See 3 more Smart Citations
“…i.e. 2×10 6 /1 kg of body mass, based on reports published by other authors and our own clinical observations (10,15,20,21,22).…”
Section: Methodsmentioning
confidence: 84%
“…MSCs are also widely used in aesthetic medicine, orthopaedics, and the treatment of growth disorders, tendinitis, or joint regeneration. In reconstructive medicine, they are commonly used in the treatment of soft tissue defects (15,27).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although most studies showed evidence that MSCs most likely act through their secretions (paracrine effect) [46][47][48] and not via their own integration/differentiation within the host tissue, some authors have reported the potential for MSCs transdifferentiation in cells of the nervous system and have shown that, after infusion into the spinal cord, these cells possibly promote regeneration of neurons because they have neuronal markers [49][50][51][52] . In vitro studies have shown that BM-MSC possess an intrinsic capacity to differentiate into neural-like and glial-like cells and express nestin, βIII-tubulin, neurofilaments, neuronspecific enolase, and glial fibrillary acidic protein (GFAP) [53][54][55] .…”
Section: Stromal Cells Therapymentioning
confidence: 99%